The Price Trap: Oversupply and Export Competition in Global Rice Trade - Mirzabaev, Alisher; Zwinger, Jeremy (International Rice Research Institute, 2025)
• World rice prices have fallen sharply in 2025 under the weight of record supplies and stocks. Across Asia, rice growers are grappling with thin or negative margins. Barring a major supply shock, the coming year may bring even lower prices. It is nearly a predictable outcome. • This is already spurring aggressive price cuts by leading exporters to maintain market share and clear stockpiles. The greatest risk is a continued price war among leading exporters – a “race to the bottom” that could push rice values to multi-year lows. In a glut, the exporter that cuts earlier tends to capture market share, while late cutters suffer steeper price declines with weaker demand response. The reality for the rice trade is that you cannot catch demand when the market is rapidly falling. • However, aggressive pricing strategies, if not mitigated by other policy interventions, often carry unintended side effects in terms of lowering farming incomes, increasing fiscal burdens, eroding exports quality, and amplifying market distortions. Falling into such a price trap may undermine long-term food security. Persistently low prices can discourage farmers from planting rice, leading to supply shortfalls later. With the market cycle at a historic high supply, a downshift has been anticipated. But the question is: How long will it last and what will the global rice trade landscape be like after it shifts?